2013
DOI: 10.1108/jhom-10-2012-0192
|View full text |Cite
|
Sign up to set email alerts
|

Work engagement as a key driver of quality of care: a study with midwives

Abstract: These results are the first to link work engagement and performance in health care contexts and point to the value of work engagement for both unit performance and for individual employee well-being in health organisations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 63 publications
4
61
0
2
Order By: Relevance
“…In previous studies of work engagement assessed by UWES, Irish nurses/ midwives, who worked as a staff on wards in 58% and as nursing managers in 26%, scored 4.26 ± 0.49 [26], and German nursing unit managers who were involved in direct patient care for 30% scored 4.29 ± 1.01 in total score [27]. These mean scores were higher than the mean score (3.12 ± 0.94) in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies of work engagement assessed by UWES, Irish nurses/ midwives, who worked as a staff on wards in 58% and as nursing managers in 26%, scored 4.26 ± 0.49 [26], and German nursing unit managers who were involved in direct patient care for 30% scored 4.29 ± 1.01 in total score [27]. These mean scores were higher than the mean score (3.12 ± 0.94) in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The engaged staff members are better equipped to deal with job demands (11). Study conducted at an Irish hospital support the importance of health service organisations deploying organisational resources to foster employee work engagement (47). Workaholism and work engagement are two different concepts that are oppositely related to well-being and performance.…”
Section: Discussionmentioning
confidence: 99%
“…Two found an indirect association between authentic leadership and engagement; 113,237 both of these studies used a self-report survey. Two further self-report studies 201,292 found a direct link between supervisory support and engagement (note also that supervisory support is frequently an aspect of job resources and hence was also reported in several studies examined in Experienced job design-related factors). Single studies found links between empowering leadership, 197 transformational leadership 133 (employee/supervisor dyad survey) or leader consideration 134 (two-wave study) and engagement.…”
Section: Perceived Leadership and Managementmentioning
confidence: 99%
“…198 social support; 201 coworker support; 292 work relationships (time-lagged study); 201 and holistic care climate. 199 Cogin and Fish 283 found that the experience of sexual harassment was negatively linked with engagement in a cross-sectional study.…”
Section: Individual Perceptions Of Organisational and Team Factorsmentioning
confidence: 99%